Correcting for physiological ripples improves epileptic focus identification and outcome prediction. Issue 2 (16th December 2021) - Zweiphenning, Willemiek J. E. M.; von Ellenrieder, Nicolás; Dubeau, François; Martineau, Laurence; Minotti, Lorella; Hall, Jeffery A.; Chabardes, Stephan; Dudley, Roy; Kahane, Philippe; Gotman, Jean; Frauscher, Birgit
Abstract: Objective: The integration of high‐frequency oscillations (HFOs; ripples [80–250 Hz], fast ripples [250–500 Hz]) in epilepsy evaluation is hampered by physiological HFOs, which cannot be reliably differentiated from pathological HFOs. We evaluated whether defining abnormal HFO rates by statistical comparison to region‐specific physiological HFO rates observed in the healthy brain improves identification of the epileptic focus and surgical outcome prediction. Methods: We detected HFOs in 151 consecutive patients who underwent stereo‐electroencephalography and subsequent resective epilepsy surgery at two tertiary epilepsy centers. We compared how HFOs identified the resection cavity and predicted seizure‐free outcome using two thresholds from the literature (HFO rate > 1/min; 50% of the total number of a patient's HFOs) and three thresholds based on normative rates from the Montreal Neurological Institute Open iEEG Atlas (https://mni‐open‐ieegatlas.research.mcgill.ca/ ): global Atlas threshold, regional Atlas threshold, and regional + 10% threshold after regional Atlas correction. Results: Using ripples, the regional + 10% threshold performed best for focus identification (77.3% accuracy, 27% sensitivity, 97.1% specificity, 80.6% positive predictive value [PPV], 78.2% negative predictive value [NPV]) and outcome prediction (69.5% accuracy, 58.6% sensitivity, 76.3% specificity, 60.7% PPV, 74.7% NPV). This was an improvement for focus identification (+1.1% accuracy, +17.0% PPV; p  < .001) and outcome prediction (+12.0% sensitivity, +1.0% PPV; p  = .05) compared to the 50% threshold. The improvement was particularly marked for foci in cortex, where physiological ripples are frequent (outcome: +35.3% sensitivity, +5.3% PPV; p  = .014). In these cases, the regional + 10% threshold outperformed fast ripple rate > 1/min (+3.6% accuracy, +26.5% sensitivity, +21.6% PPV; p  < .001) and seizure onset zone (+13.5% accuracy, +29.4% sensitivity, +17.0% PPV; p  < .05–.01) for outcome prediction. Normalization did not improve the performance of fast ripples. Significance: Defining abnormal HFO rates by statistical comparison to rates in healthy tissue overcomes an important weakness in the clinical use of ripples. It improves focus identification and outcome prediction compared to standard HFO measures, increasing their clinical applicability.